2008
DOI: 10.1111/j.1523-1739.2008.00998.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Changes in Amphibian Population Dynamics Following Experimental Manipulations of Introduced Fish

Abstract: Sport-fish introductions are now recognized as an important cause of amphibian decline, but few researchers have quantified the demographic responses of amphibians to current options in fisheries management designed to minimize effects on sensitive amphibians. Demographic analyses with mark-recapture data allow researchers to assess the relative importance of survival, local recruitment, and migration to changes in population densities. I conducted a 4-year, replicated whole-lake experiment in the Klamath Moun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 36 publications
3
53
0
Order By: Relevance
“…For instance, the removal of fish from lakes allowed the restoration of frog and salamander populations (Vredenburg 2004;Knapp et al 2007;Pope 2008). This resilience was enhanced in many species of bi-phasic amphibians that are able to disperse on land, and can thus colonise managed aquatic habitats from nearby wetlands.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…For instance, the removal of fish from lakes allowed the restoration of frog and salamander populations (Vredenburg 2004;Knapp et al 2007;Pope 2008). This resilience was enhanced in many species of bi-phasic amphibians that are able to disperse on land, and can thus colonise managed aquatic habitats from nearby wetlands.…”
Section: Introductionmentioning
confidence: 98%
“…However, amphibians could rapidly recover, reaching the same population sizes as in control lakes in only a few years (Funk and Dunlap 1999;Vredenburg 2004;Knapp et al 2007;Pope 2008). The exact dates of fish introduction and extirpation are not known for all sites in Larzac.…”
Section: Resilience Of Newts and Re-expression Of Paedomorphosismentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, some declines caused by alien species may be reversed relatively quickly (Pope 2008;Knapp et al, 2007;Mullin 2004;Vredenburg 2004). In California, reversal of the negative effects of alien species on amphibians has been suggested by a number of studies showing that the removal or disappearance of the alien species results in the recovery of local amphibian populations (Pope et al, 2008;Knapp et al, 2001;Knapp 2005;Vredenburg 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In California and much of western North America, amphibian population declines are occurring, and several causal factors have been proposed including disease Kiesecker et al, 2001;Blaustein et al, 2005;, increased use of pesticides and air pollution (Davidson et al, 2001;Relyea and Mills 2001;Kiesecker 2002), habitat destruction (Davidson et al, 2002), over-exploitation (Jensen and Camp 2003;Jennings and Hayes 1985), climate change (Pounds et al, 1999), UV-B radiation Anzalone et al, 1998;Blaustein et al,1998), and alien predators and competitors (Kupferburg 1997;Knapp and Matthews 2000;Vredenburg 2004;Pope 2008). Recent studies have suggested that amphibian declines are potentially influenced by a number of contextspecific interactions of multiple stressors and synergisms between these causal factors (Blaustein and Kiesecker 2002;Kiesecker 2002;Pounds et al, 2006).…”
Section: Introductionmentioning
confidence: 99%